Formative-reflective process for the rational use of medicines in the settlements of the municipality of Pontão/Rs: ForThe report of an experience in the light of Freirean teachings - Glusczak, Lissandra; Siles Barduco, Eliseu; Haack, Marcos; Chiodi Agostini, Camila; Braga Simonetti, Amauri; Muller Germani, Alessandra Regina; Nenê Portela, Silvane; Tuzzin, Leandro; Knop, Marione (Guará Journal, 2019)
This experience report describes the experience of a group of people formed by medical students from the Federal University of São Paulo (UFFS/Campus Passo Fundo), professors, technical-administrative staff, and a preceptor from the municipality of Pontão, Rio Grande do Sul, in an extension project focused on the rational use of medications for a population of settlers in that municipality. A specific methodology based on Freirean teachings was used for the work, which provided the theoretical foundation for the activity. The activities were developed over six meetings with the selected population, in a community space within the settlement of the former Anonni Farm, where topics related to the rational use of medications were addressed. The experience highlighted the need for a continued approach by health professionals regarding the importance of the rational use of medications and the dangers of self-medication. During the development of the project activities, the dynamics and language used were adapted to obtain maximum participation from the settlers. We concluded that the development of this outreach project enabled effective communication with the settler community, enabling an exchange of knowledge where we learned more about their realities and perceptions regarding medication use, as well as jointly building knowledge about the proposed topics. In this same sense, we noted the importance of using the reflective training process advocated by Freire to develop awareness about the rational use of medication.